2003
DOI: 10.1074/mcp.m300088-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

A Proteomic Analysis of Arginine-methylated Protein Complexes

Abstract: Arginine methylation is a post-translational modification that results in the formation of asymmetrical and symmetrical dimethylated arginines (a-and sDMA). This modification is catalyzed by type I and II protein-arginine methyltransferases (PRMT), respectively. The two major enzymes PRMT1 (type I) and PRMT5 (type II) preferentially methylate arginines located in RG-rich clusters. Arginine methylation is a common modification, but the reagents for detecting this modification have been lacking. Thus, fewer than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
292
2
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 338 publications
(308 citation statements)
references
References 80 publications
10
292
2
4
Order By: Relevance
“…PRMT1 is the predominant and essential arginine methyltransferases in human cell, responsible for at least 85% of all arginine methylation reactions [24]. This result is consistent with the findings that most of the identified substrates are catalysed by PRMT1 [25,26], and that PRMT1 is vital for the early development of mice in that PRMT1 À/À mice die beyond embryonic days 6.5 [27]. PRMT1 is believed to preferentially catalyse proteins that interact with nucleic acids, such as histone H3 and H4, components of hnRNP, fabrillarin and nucleolin, to regulate protein-protein interactions [26].…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…PRMT1 is the predominant and essential arginine methyltransferases in human cell, responsible for at least 85% of all arginine methylation reactions [24]. This result is consistent with the findings that most of the identified substrates are catalysed by PRMT1 [25,26], and that PRMT1 is vital for the early development of mice in that PRMT1 À/À mice die beyond embryonic days 6.5 [27]. PRMT1 is believed to preferentially catalyse proteins that interact with nucleic acids, such as histone H3 and H4, components of hnRNP, fabrillarin and nucleolin, to regulate protein-protein interactions [26].…”
Section: Introductionsupporting
confidence: 90%
“…So far the functional consequence of arginine methylation by PRMT is much less understood than those of the other post-translation modifications such as phosphorylation or acetylation. However, a recent proteomic study using four arginine methyl-specific antibodies has identified over 200 putative methylated proteins, which show that arginine methylation may be required for many cellular processes including signal transduction, the cytoskeleton, DNA repair, transcription, translation, and apoptosis [25]. In this study, flounder PoPRMT1 gene was cloned and the up-regulation by virus infection was verified in vitro and in vivo, indicating that PoPRMT1 might be implicated in fish antiviral immune response.…”
Section: Discussionmentioning
confidence: 84%
“…Protein arginine methyltransferase 1 is a multifunctional protein, implicated in diverse biological processes, such as DNA repair, signal transduction, protein trafficking and RNA processing (McBride and Silver, 2001;Boisvert et al, 2003;Bedford and Richard, 2005;Lee et al, 2005b). Protein arginine methyltransferase 1 methylates a number of hnRNP molecules, playing a role in the shuttling of these proteins between the cytoplasm and the nucleus (Herrmann et al, 2004), and histone H4 at arginine 3 (Wang et al, 2001), a modification that functions as a transcription activation mark.…”
mentioning
confidence: 99%
“…Interestingly, this region contains an arginine-methyltransferase target sequence (amino acids 939-947). 43 Arginine methylation is important for transcriptional activation of nuclear receptor transcription complexes, 44 and given MN1's interaction with RARa-RXR dimers, 34 this methylation sequence might contribute to MN1's function, a possibility we are investigating.…”
Section: Discussionmentioning
confidence: 99%